Step-by-step explanation: Since both terms are perfect cubes, we can factor using the sum of cubes formula which is a^3 + b^3 = (a + b)(a^2 – ab + b^2) where a = 5x and b = 3y^6. Our factored equation would look like 4(5x + 3y^6)(25x^2 – 15xy^6 + 9y^12) with the factors being 4, (5x + 3y^6), and (25x^2 – 15xy^6 + 9y^12)

## Answers ( )

Answer: Your answer will be B)Step-by-step explanation: Since both terms are perfect cubes, we can factor using the sum of cubes formula which is a^3 + b^3 = (a + b)(a^2 – ab + b^2) where a = 5x and b = 3y^6. Our factored equation would look like 4(5x + 3y^6)(25x^2 – 15xy^6 + 9y^12) with the factors being 4, (5x + 3y^6), and (25x^2 – 15xy^6 + 9y^12)